UGT1A1 rs4148323 A Allele is Associated With Increased 2-Hydroxy Atorvastatin Formation and Higher Death Risk in Chinese Patients With Coronary Artery Disease - Lei, He-Ping; Qin, Min; Cai, Li-Yun; Wu, Hong; Tang, Lan; Liu, Ju-E; Deng, Chun-Yu; Liu, Yi-Bin; Zhu, Qian; Li, Han-Ping; Hu, Wei; Yang, Min; et al. (Frontiers in Pharmacology, 2021)
It is widely accepted that genetic polymorphisms impact atorvastatin (ATV) metabolism, clinical efficacy, and adverse events. The objectives of this study were to identify novel genetic variants influencing ATV metabolism and outcomes in Chinese patients with coronary artery disease (CAD). A total of 1079 CAD patients were enrolled and followed for 5 years. DNA from the blood and human liver tissue samples were genotyped using either Global Screening Array-24 v1.0 BeadChip or HumanOmniZhongHua-8 BeadChip. Concentrations of ATV and its metabolites in plasma and liver samples were determined using a verified ultra-performance liquid chromatography mass spectrometry (UPLC-MS/MS) method. The patients carrying A allele for the rs4148323 polymorphism (UGT1A1) showed an increase in 2-hydroxy ATV/ATV ratio (P = 1.69E-07, false discovery rate [FDR] = 8.66E-03) relative to the value in individuals without the variant allele. The result was further validated by an independent cohort comprising an additional 222 CAD patients (P = 1.08E-07). Moreover, the rs4148323 A allele was associated with an increased risk of death (hazard ratio [HR] 1.774; 95% confidence interval [CI], 1.031-3.052; P = 0.0198). In conclusion, our results suggested that the UGT1A1 rs4148323 A allele was associated with increased 2-hydroxy ATV formation and was a significant death risk factor in Chinese patients with CAD.